POSTGRADUATE STUDIES IN THE THEORY AND METHODS OF TEACHING MATHEMATICS: CURRENT EXPERIENCE AND DEVELOPMENT DIRECTIONS - Mykhailenko, Lyubov; Khutchenko, Ivan (Physical and Mathematical Education, 2025)
Formulation of the problem. The training of research personnel in the theory and methods of teaching mathematics and the engagement of young scholars in the academic community is a pressing issue. In Ukraine, only four dissertations have been defended in the last five years in the specialty 014 Secondary Education (Mathematics), highlighting a critical need to modernize approaches to PhD and EdD training.Materials and methods. The study examines the experience of training Doctor of Philosophy (PhD) and Doctor of Education (EdD) graduates in mathematics education in the USA, the UK, and China, based on academic publications, OECD reports, and national educational strategies.Results. China's PhD training system demonstrates dynamic growth and ranks among the world's leaders in terms of the number of doctoral candidates and research funding. The country's education policy focuses on attracting talented students, fostering mentorship, and integrating research personnel into school education, driving innovation. The study explores the current directions of mathematics education research training in the UK, based on three leading universities. The characteristics of PhD and EdD programs, their requirements, structure, and graduates’ prospects in the international academic environment are outlined. The study also examines trends in doctoral training in mathematics education in the USA, highlighting the specifics of PhD and EdD programs, their requirements, career prospects, and educational content. The analysis covers online learning opportunities, course structure, internships, final assessments, research components, and differences in preparing educational leaders versus researchers in mathematics education.  Conclusion. A key direction for developing postgraduate studies in the theory and methods of teaching mathematics is the implementation of EdD programs in mathematics education, tailored to practicing teachers and educational leaders. Further research should focus on expanding practical training and improving state policies to support young researchers.
Keywords: postgraduate studies in the theory and methods of teaching mathematics; Doctor of Philosophy; research and teaching personnel in mathematics education